Palynological Studies of Three Taxa and One F1 Hybrid in the Genus Talinum Adans - Oluwabunmi Okerinmola AROGUNDADE; Hameedat O. LAWAL (Notulae Scientia Biologicae, 2018)
Acetolysed pollen grains of Talinum paniculatum (Jacq.) Gaertn., Talinum triangulare (Jacq.) Willd. pink petals, Talinum triangulare (Jacq.) Willd. white petals and Talinum triangulare (Jacq.) Willd. pink and white petals F1 hybrid were studied in order to document their morphological structures and ascertain features of taxonomic significance among them. All the taxa have generic features which support their classification as a genus as well as distinct features which ascertain their individuality. Generic features include monad pollen unit, acolpate and monocolpate pollen grains as well as circular and ovate pollen shapes. The delimiting features include additional dyads pollen units in T. triangulare white petal and the F1 hybrid of T. triangulare pink and white petals, quadrangular pollen shape in T. paniculatum, bicolpate pollen grain in the F1 hybrid, tricolpate pollens in   T. triangulare white petal and T. paniculatum, tetracolpate pollens in T. triangulare pink petal and T. paniculatum and pentacolpate pollen grains in T. paniculatum only. The shape of the pores in T. paniculatum also separated it from the varieties and hybrid of T. triangulare. Based on the pollen size, the pollens of T. paniculatum are Media (25 - 50 µm) while those of the two varieties of T. triangulare and their F1 hybrid are Magna (50 - 100 µm). The taxa of Talinum in this study can be separated based on their palynological features.